2021
DOI: 10.1002/rcm.9197
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted metabolomic study of HepG2 cells under the effect of Fucus vesiculosus aqueous extract

Abstract: Bioisi MassSpec FacilityRationale: Fucus vesiculosus has been described with potential to develop functional foods containing bioactive compounds against various diseases. However, more studies are needed to better understand its functioning and its previously reported bioactivities, mainly at the molecular level.Methods: An untargeted metabolomic study was performed to analyse HepG2 cells exposed to F. vesiculosus aqueous extract, rich in phlorotannins and peptides, during 24 h. This study was carried out usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In the cells treated with Aramé extract, a decrease in the level of GSH was detected relative to the control cells, which can be associated with a higher utilization rate of this metabolite inside the treated cells, a mechanism important to prevent oxidative stress. A modification in glutathione metabolism was seen in Hep-G2 cells exposed to a brown seaweed Fucus vesiculosus extract [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the cells treated with Aramé extract, a decrease in the level of GSH was detected relative to the control cells, which can be associated with a higher utilization rate of this metabolite inside the treated cells, a mechanism important to prevent oxidative stress. A modification in glutathione metabolism was seen in Hep-G2 cells exposed to a brown seaweed Fucus vesiculosus extract [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Both of these types of metabolites may be related to modifications in the metabolism of lipids, proteins, and amino acids due to exposure to the Nori extract. In the case of fatty acid amides, it was already reported that Hep-G2 metabolites were modified by a Fucus vesiculosus extract [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, decanamide is only referred to as a minor metabolite of the bacterium Pseudomonas X2 when grown with n-decane as its only carbon source [ 36 ]. In contrast, dodecanamide, palmitamide, stearamide, oleamide, and linoleamide were all produced by HepG2 cells treated with extracts of the brown algae Fucus vesiculosus [ 37 ]. Dodecanamide has been reported as an intracellular metabolite in MCF-7 cells after doxorubicin-induced cell death [ 38 ] and with diminished levels in the serum of acute myeloid leukemia patients who responded well to chemotherapy with cytarabine plus anthracycline [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dodecanamide has been reported as an intracellular metabolite in MCF-7 cells after doxorubicin-induced cell death [ 38 ] and with diminished levels in the serum of acute myeloid leukemia patients who responded well to chemotherapy with cytarabine plus anthracycline [ 39 ]. There exist more extensive studies in the literature on palmitamide, palmitoleamide, stearamide, oleamide, and linoleamide [ 37 , 40 , 41 , 42 , 43 , 44 ], but none in relation to HCV and the liver, with the exception of oleamide in our earlier metabolomics report on HCV-infected patients [ 28 ]. Therefore, our description of these seven FAAs elevated due to HCV infection is novel, which is additionally supported by our observation that the FAA catabolic enzyme FAAH2 showed a 40% decrease ( p = 0.03) in mRNA expression due to HCV.…”
Section: Discussionmentioning
confidence: 99%
“…30 The reported activities did coincide with the clinical efficacy of CNL granule. Kaempferol-7-O-neohesperidoside was tested for antitumor activity and exhibited potent activities against HepG2 31 and Hela 32 with IC 50 values of 0.020 and 0.051 μM, respectively. Given its potent toxicity against tumor cells, its toxicity toward normal human cells is to be tested before these analogues can be taken as the bioactive material basis of CNL granule.…”
Section: Chemical Constituent Comparison Between the Two Extractsmentioning
confidence: 99%